2002
DOI: 10.1046/j.1365-2133.2002.05037.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated T-cell lymphoma: a case of eyelid swelling and intramuscular infiltration mimicking dermatomyositis

Abstract: Association with Epstein-Barr virus (EBV) infection has been noted in various types of cutaneous lymphoproliferative disorders. We report a 57-year-old Japanese woman with T-cell lymphoma mimicking dermatomyositis that was associated with chronic active EBV infection. She presented with low-grade fever, bilateral erythematous swellings on the eyelids, and necrotic papules on the face. Serum creatine kinase levels were elevated and a diffuse reticular shadow was detected in both lung fields. The infiltrate of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…2, and whose onsets were clear after 20 years of age. Eighteen reported patients were selected as shown in Table 2 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Analysis Of Reported Casesmentioning
confidence: 99%
“…2, and whose onsets were clear after 20 years of age. Eighteen reported patients were selected as shown in Table 2 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Analysis Of Reported Casesmentioning
confidence: 99%
“…Many studies have shown that the expression of viral latent genes, especially genes for EBNAs (EBV-associated nuclear antigens) and LMP-1 (latent membrane protein-1), has been closely associated with latent infection that correlates with immortalization and tumorigenesis. In recent years, more evidences show that EBV is found in tumors of bladder [6], breast [7], cervix [8], gastric [9] or gastrointestinal tract [10], kidney [11], lung [12], skin [13], and thyroid [14]. Unfortunately, the role of the virus in the formation of these cancers remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Ohtsuka et al 3,8 and Shirasaki et al 9 have reported similar cases with erythematous swelling of the eyelids and intramuscular infiltration mimicking DM that was associated with chronic active EBV infection. The initial clinical manifestations in our patient were also suggestive of DM; namely, bilateral eyelid swelling, erythematous rash over the extremities, and muscular weakness.…”
Section: Discussionmentioning
confidence: 92%